Developing an E-Big Book Assisted Global Method to Improve Information Narrative Text Comprehension among Elementary School Students - Panca Dewi Purwati; Faradila, Malika Aulia (Journal of Integrated Elementary Education, 2025)
Low reading comprehension among first-grade students presents a significant educational challenge. This study addresses this issue through a Research and Development (R&D) approach to design, validate, and evaluate the effectiveness of an e-big book based on the local wisdom of the Prophet's Maulid Tradition, assisted by the Global Method. The development process followed an eight-stage adaptation of the Borg and Gall model, involving first-grade students and teachers from SDN 1 and SDN 3 Kedungsuren, Kendal, as well as media and material experts for validation. Data were collected through observations, interviews, questionnaires, and pre-post tests, and were analyzed using descriptive statistics, Paired Sample T-Tests, and N-Gain calculations. The results demonstrated high feasibility, with validation scores of 92% from the media expert and 93% from the material expert. Furthermore, the product proved highly effective in improving students' narrative text comprehension, as indicated by a significant increase in learning outcomes and a Normalized Gain score of 0.7508, which falls into the "high effectiveness" category. This study concludes that the developed e-big book is a valid, practical, and effective instructional medium that successfully integrates local culture and pedagogical theory to enhance early literacy skills.